VARK: Kajian Survei dalam Domain Kognitif Keilmuan dari Mahasiswa Sebuah Universitas Terbesar di Kota Surakarta - Hernawan Sulistyanto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research is a quantitative study that examines the preferences of Visual, Auditory,Read/Write, Kinesthetic (VARK) learning styles in the scientific cognitive domain. Threegroups of students with different scientific backgrounds were compared to obtain the latestfacts about differences in learning style preferences. Data was collected online based onthe VARK questionnaire version 7.1 of 270 students in three different study programs froma public university in Surakarta City, Indonesia. The results show that the differences inknowledge being studied by students in different study programs make a significantcontribution to the differences in learning style preferences of each student. However, thedifference is not much difference between students in the same study program, both maleand female. This difference in learning style preferences provides a sign for educators todesign innovative learning process models that are tailored to students' learning stylepreferences.